Dynamin-related proteins in plant post-Golgi traffic - Fujimoto, Masaru; Tsutsumi, Nobuhiro (Frontiers in Plant Science, 2014)
Membrane traffic between two organelles begins with the formation of transport vesicles from the donor organelle. Dynamin-related proteins (DRPs), which are large multidomain GTPases, play crucial roles in vesicle formation in post-Golgi traffic. Numerous in vivo and in vitro studies indicate that animal dynamins, which are members of DRP family, assemble into ring- or helix-shaped structures at the neck of a bud site on the donor membrane, where they constrict and sever the neck membrane in a GTP hydrolysis-dependent manner. While much is known about DRP-mediated trafficking in animal cells, little is known about it in plant cells. So far, two structurally distinct subfamilies of plant DRPs (DRP1 and DRP2) have been found to participate in various pathways of post-Golgi traffic. This review summarizes the structural and functional differences between these two DRP subfamilies, focusing on their molecular, cellular and developmental properties. We also discuss the molecular networks underlying the functional machinery centering on these two DRP subfamilies. Furthermore, we hope that this review will provide direction for future studies on the mechanisms of vesicle formation that are not only unique to plants but also common to eukaryotes.